Pengaruh Motivasi Kerja dan Kompensasi Terhadap Kinerja Karyawan PT.Tiki Jalur Nugraha Ekakurir di Kantor Cabang Utama Semarang - Adinda Putri Hermansya; Sri Nawatmi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the effect of work motivation and compensation on employee performance. This research was conducted at PT Tiki Jalur Nugraha Ekakurir using employees from several departments as samples, with a total sample of 101 employees. The research results show that work motivation has a positive effect on employee performance. Meanwhile, compensation has a negative effect on employee performance. In this research, the most influential variable is the work motivation variable.